REJECTION OF POLYGAMY PERMISSION BY THE LUBUK PAKAM RELIGIOUS COURT FROM THE PERSPECTIVE OF MAQASHID SYARI'AH (ANALYSIS OF DECISION NUMBER 0007/PDT.G/2019/PA.LPK) - Dina Sakinah Siregar (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2025)
This research examines the rejection of the Polygamy Permit of the Lubuk Pakam Religious Court in the Perspective of Maqashid Syari'ah (Review of Decision Number 0007 / Pdt.G / 2019 / PA.Lpk). From the research results it is concluded that: first, Islamic law regulates polygamy in QS. An-Nisa verse 3 that it is permissible to do polygamy on fair terms to his wives. Meanwhile, the Law regulates polygamy in Law No. 1 of 1974 Articles 4 and 5, Goverment Regulation No. 9 of 1975 Articles 40-44 and KHI in articles 55-59. Second, the Judge's consideration in deciding case Number 0007 / Pdt.G / 2019 / PA.Lpk was because according to the Panel of Judges the applicant's request did not meet the facultative requirements. Third, according to theanalysis maqashid shari'ah there is a mafsadah that will be generated in this case, whether this case is accepted or rejected. Whereas according to the author's analysis, the decision of the Panel of Judges to reject the application for a polygamy permit is legally correct, but from the point of view of maqashid syari'ah, refusal of a polygamy permit is considered inappropriate. As thefiqh law ofDar'ul Mafasid Muqaddam 'Ala Jalb Al-Mashalih, in terms of refusing this request for polygamy, the author feels that maintaining offspring and self-respect are considered more important. Therefore, the refusal of polygamy permission according to the author's analysis is considered inappropriate from the point of view of maqashid shari'ah. In line with the above conclusions, the government should make clear statutory regulations, for judges or readers the analysis of maqashid syari'ah in this case should not be used as an absolute benchmark because in-depth analysis is needed for those who wish to practice polygamy it should fulfill all the terms of the applicable law.